Enantioselective Hydroxylation of Dihydrosilanes to Si‐Chiral Silanols Catalyzed by In Situ Generated Copper(II) Species - Yang, Wu; Liu, Lin; Guo, Jiandong; Wang, Shou‐Guo; Zhang, Jia‐Yong; Fan, Li‐Wen; Tian, Yu; Wang, Li‐Lei; Luan, Cheng; Li, Zhong‐Liang; He, Chuan; Wang, Xiaotai; et al. (Angewandte Chemie International Edition, 2022)
Catalytic enantioselective hydroxylation of prochiral dihydrosilanes with water is expected to be a highly efficient way to access Si‐chiral silanols, yet has remained unknown up to date. Herein, we describe a strategy for realizing this reaction: using an alkyl bromide as a single‐electron transfer (SET) oxidant for invoking CuII species and chiral multidentate anionic N,N,P‐ligands for effective enantiocontrol. The reaction readily provides a broad range of Si‐chiral silanols with high enantioselectivity and excellent functional group compatibility. In addition, we manifest the synthetic potential by establishing two synthetic schemes for transforming the obtained products into Si‐chiral compounds with high structural diversity. Our preliminary mechanistic studies support a mechanism involving SET for recruiting chiral CuII species as the active catalyst and its subsequent σ‐metathesis with dihydrosilanes. Copper(II)‐mediated σ‐metathesis with prochiral dihydrosilanes has been successfully leveraged to efficiently synthesize Si‐chiral silanols as well as many other related Si‐chiral skeletons. The reaction hinges on the continuous generation of catalytically active copper(II) species via single‐electron transfer oxidation of copper(I) by alkyl halides and the efficient stereocontrol with multidentate anionic N,N,P‐ligands.